β-thalassemia intermedia in a Brazilian patient with - 101(C > T) and codon 39 (C > T) mutations - Sousa, Sylvia Morais de (2003)
CONTEXT: We verified molecular alterations in a 72- year-old Brazilian male patient with a clinical course of homozygous β-thalassemia intermedia, who had undergone splenectomy and was surviving without regular blood transfusions. The blood cell count revealed microcytic and hypochromic anemia (hemoglobin = 6.5 g/dl, mean cell volume = 74 fl, mean cell hemoglobin = 24 pg) and hemoglobin electrophoresis showed fetal hemoglobin = 1.3%, hemoglobin A2 = 6.78% and hemoglobin A = 79.4%. OBJECTIVE: To identify mutations in a patient with the symptoms of β-thalassemia intermedia. DESIGN: Molecular inquiry into the mutations possibly responsible for the clinical picture described. SETTING: The structural molecular biology and genetic engineering center of the Universidade Estadual de Campinas, Campinas, Brazil. PROCEDURES: DNA extraction was performed on the patient’s blood samples. The polymerase chain reaction (PCR) was done using five specific primers that amplified exons and the promoter region of the β globin gene. The samples were sequenced and then analyzed via computer programs. RESULTS: Two mutations that cause the disease were found: -101 (C > T) and codon 39 (C > T). CONCLUSIONS: This case represents the first description of –101 (C > T) mutation in a Brazilian population and it is associated with a benign clinical course.